Legal Analysis of Criminalization of Children Perpetrators of the Crime of Theft with Aggravation Based on Pancasila Justice (Criminal Case Study Decision Number: 57/Pid.B/2024/PN Nab) - Satria, Rifai Ermin; Hafidz, Jawade (UNISSULA Semarang, 2025)
Abstract. Law is a norm or rule that contains mandatory legislation and anyone who violates the article will receive legal sanctions. The legal subjects who are to be prosecuted are not only those who have actually committed unlawful acts, but also legal acts that may arise and equip the state to act in accordance with the laws currently in force. Crime is an offense, namely things that are contrary to or in conflict with the legal principles that are the beliefs of human life and are not bound by law. Crimes that often occur in society lately include robbery, burglary, murder and rape. One type of crime that often occurs in society is theft. The crime of theft is a crime that is officially stipulated as prohibited and punishable, in this case it is an act defined as